(3eUGOQ GdGdJRGe aj VhA bhGYO Gdabg GdESdGej hGdCfXeI GdSYhOjI hGdGLJgGOGJ GdbVGFjI GdYQHjI hGdaQfSjI (B:s (3OQGSI ebGQfI (B= Sources of obligations in the Light of the islamic jurisprudence the saudi systems, and arabic and french judicial efforts : a comparative study : (3GdeUGOQ GdEQGOjI(B-(3GdYbO hGdEQGOI GdefaQOI (B/s - (3HdMGL, GdYQHjs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2017)
(3gPg OQhS aj eGOI (B"(3eUGOQ GdGdJRGe(B" (3aj VhA bhGYO Gdabg GdESdGej hGdCfXeI GdSYhOjI hGdGLJgGOGJ GdbVGFjI GdYQHjI hGdaQfSjI GdeTghQI, hgj NdGUI efXeI ddeMGVQGJ GdJj CdbjJgG Ydi WdGH cdjI GdMbhb aj LGeYI Gdedc YHO GdYRjR HLOI, NdGd GdYGe GdLGeYj (B2013-2014 (3ejdGOj, hjJfGhd GdcJGH GdLRA GdChd aj TQM GdfXQjI GdYGeI ddGdJRGeGJ hYhdLJ ajg GdeUGOQ GdEQGOjI ddGdJRGe (B((3GdJUQa GdbGfhfj(B)(3, hgj GdYbO hGdEQGOI GdefaQOI, hgPg GdOQGSI deUGOQ GdGdJRGeGJ GdEQGOjI, hgj OQGSI Ydi SHjd GdebGQfI, heG NdU Edjg abgGA GdTQjYI GdESdGejI GdZQGA, hcPG GdebGHdI eY HYV GdJTQjYGJ GdYQHjI, hGdbGfhf GdeOfj GdaQfSj aj bdjd Ce cKjQ, HeG jJfGSH eY GdeQMdI GdLGeYjI(B.s
(3eMce YdejG(B.s
(3HHdjhLQGajI (B: (3UaMI (B597-622.s
Keywords: (3GdGdJRGeGJ (B((3abg ESdGej(B)s; (3GdGdJRGeGJs -- (3bhGfjf hJTQjYGJs -- (3GdSYhOjIs; (3GdGdJRGeGJs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdGdJRGeGJs -- (3bhGfjf hJTQjYGJs -- (3aQfSGs